Project-Based Learning with Scratch to Improve Students’ Creative Thinking Ability: Systematic Literature Review - Winarko, Gemintang Cinta (Griya Journal of Mathematics Education and Application, 2024)
Creative thinking abilities are crucial for students, particularly within the realm of mathematics, to tackle real-world challenges effectively. Regrettably, many students encounter difficulties in nurturing their creative thinking abilities due to the inadequate teaching methods and educational resources employed by instructors. As a result, there is a pressing demand for inventive teaching approaches and materials, with project-based learning using Scratch emerging as one such innovative method to foster students' creative thinking proficiencies. This research, which encompassed a systematic review, concludes that the utilization of the Project-based Learning approach with Scratch as an educational tool can indeed enhance students' creative thinking abilities in the context of mathematics education. Furthermore, it recommends further development by harnessing applications like Scratch or other visual programming tools and exploring alternative research models for comparative analysis.